2009
DOI: 10.1136/bcr.12.2008.1317
|View full text |Cite
|
Sign up to set email alerts
|

Can posterior hip fracture-dislocation occur in indoor football (futsal)? A report of two cases

Abstract: Hip fracture-dislocation is extremely rare in sports and is most frequently seen after road traffic accidents. This injury is associated with considerable long-term disability and rapidly progressive joint degeneration. This case report illustrates two cases of hip fracture dislocation that occurred while playing recreational indoor football (futsal). Futsal is a fast-emerging recreational sport in Malaysia and we are now beginning to see high-impact injuries rarely encountered in recreational sports. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…But to our knowledge, there is no case reported that have a pure hip dislocation when playing non-contact sport like tennis. In English literature there are 21 traumatic hip dislocations with and without fracture in sports activity [2][3][4][5][6][7][8]. Among all these -6 rugby, 5 soccer, 2 futsal and one each water skiing, equestrian, gymnastic, jogging, skiing, biking, sledge, basketball player had traumatic hip dislocation-only five of them were pure dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…But to our knowledge, there is no case reported that have a pure hip dislocation when playing non-contact sport like tennis. In English literature there are 21 traumatic hip dislocations with and without fracture in sports activity [2][3][4][5][6][7][8]. Among all these -6 rugby, 5 soccer, 2 futsal and one each water skiing, equestrian, gymnastic, jogging, skiing, biking, sledge, basketball player had traumatic hip dislocation-only five of them were pure dislocations.…”
Section: Discussionmentioning
confidence: 99%